Checklist of bat flies (Diptera: Nycteribiidae and Streblidae) and their associated bat hosts in Malaysia - Isham, Azhar; Faisal Ali, Anwarali Khan; Norwahidah, Ismail; Abdullah, M.T (Check List and Authors, 2015)
The number of publications on bat flies of Malaysia suggests that this group of parasitic dipterans is understudied. From April 2011 to September 2013, we surveyed 10 localities from seven states in Malaysia with the main objective to compile a checklist of bat flies. As a result, a total of 15 species of bat flies were recorded from 24 species of hosts. Our surveys indicated that there is a correlation between the number of bat species and the number of bat flies species recorded due to the host specific nature of bat flies.